2015
DOI: 10.1142/s0218271815500558
|View full text |Cite
|
Sign up to set email alerts
|

Induced vacuum bosonic current by magnetic flux in a higher dimensional compactified cosmic string spacetime

Abstract: In this paper, we analyse the bosonic current densities induced by a magnetic flux running along an idealized cosmic string in a high-dimensional spacetime, admitting that the coordinate along the string's axis is compactified. Additionally we admit the presence of an magnetic flux enclosed by the compactification axis. In order to develop this analysis we calculate the complete set of normalized bosonic wave-functions obeying a quasiperiodicity condition, with arbitrary phase β, along the compactified dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
(78 reference statements)
5
42
0
Order By: Relevance
“…The above axial current density, in the massless limit, matches to the result for the Minkowski spacetime times the conformal factor (τ /α) 4 (the sign of the axial current obtained in [34] should be corrected to the opposite one).…”
Section: Axial Currentsupporting
confidence: 80%
See 2 more Smart Citations
“…The above axial current density, in the massless limit, matches to the result for the Minkowski spacetime times the conformal factor (τ /α) 4 (the sign of the axial current obtained in [34] should be corrected to the opposite one).…”
Section: Axial Currentsupporting
confidence: 80%
“…The summation above has been developed in [34]. The result is The integral over z can be evaluated with the help of the formula [43] ∞…”
Section: Azimuthal Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason is in the expression for the function g(q, α 0 , 2y), Eq. (40), that appears in the integral. Being α 0 = 0, there are no hyperbolic cosines involving the variable of integration, y, and the integral is finite.…”
Section: Vacuum Expectation Value (Vev) Of the Energy-momentum Tensormentioning
confidence: 99%
“…In all these analysis, the authors have shown that induced azimuthal vacuum current densities take place if the ratio of the magnetic flux by the quantum one has a nonzero fractional part. In fact, induced fermionic and scalar current densities in compactified cosmic string spacetimes have been considered in [15,16].…”
Section: Introductionmentioning
confidence: 99%